2020
DOI: 10.3390/agronomy10050706
|View full text |Cite
|
Sign up to set email alerts
|

A Phenotypic Search on Graft Compatibility in Grapevine

Abstract: Grafting is the most used propagation method in viticulture and is the unique control strategy against Phylloxera. Nevertheless, its practice remains limited mainly due to inconsistent graft success and difficulties in predicting graft compatibility responses of proposed scion–rootstock combinations, slowing down the selection of elite rootstocks. Aiming to identify optimal phenotypic parameters related to graft (in)compatibility, we used four clones of two grapevine cultivars that show different compatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
(80 reference statements)
1
23
0
1
Order By: Relevance
“…As the performance of a grafted plant and the commercial application of the rootstock not only depends on the genotype of scion and rootstock, but also the compatibility of the rootstock with scion [ 16 18 ], it is necessary to examine the graft combination of breadfruit/marang for graft compatibility. Anatomy examination of a scion/rootstock union has been a method that unambiguously identifies graft incompatibility in woody species [ 19 21 ]. Anatomy examination of graft interface was first carried out on the graft unions of three interspecific grafts at 26 months after grafting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the performance of a grafted plant and the commercial application of the rootstock not only depends on the genotype of scion and rootstock, but also the compatibility of the rootstock with scion [ 16 18 ], it is necessary to examine the graft combination of breadfruit/marang for graft compatibility. Anatomy examination of a scion/rootstock union has been a method that unambiguously identifies graft incompatibility in woody species [ 19 21 ]. Anatomy examination of graft interface was first carried out on the graft unions of three interspecific grafts at 26 months after grafting.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that the breadfruit/marang grafts had good compatibility with hardly visible graft lines in bark and wood (category ‘A’, see Methods, also [ 22 ]) and there was no discontinuities along the graft lines between bark and wood in all the graft unions examined (see example image in Figure S 2 ). The ratio of the stem diameter above and below the graft union has often been used to correlate growth characteristics with graft incompatibility [ 19 21 ]. In consistent with the anatomy assessment, the ratio of scion to rootstock stem diameter in the breadfruit/marang combination was very close to 1, and there was no significant difference between those of the self-graft and the interspecific graft (Table S 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In grapevine it was found that it is not the graft take rates but the status of callus formation at 21 DAG which is an indicative of compatibility between the stock and scion. Moreover, analysis of leaf chlorophyll content can also serve as an efficient means to estimate the compatibility ( Tedesco et al, 2020 ). The difference in the quality and quantity of phenol in the stock and scion can point toward metabolic dysfunctions at the graft union ( Errea, 1998 ) and can serve as a biochemical marker to predict graft incompatibility ( Musacchi et al, 2000 ).…”
Section: Graft Incompatibility: Types and Determining Techniquesmentioning
confidence: 99%
“…The causes of graft incompatibility are multiple; genetic proximity, poor craftsmanship, climatic conditions or pathogens can harm a successful graft union formation and maintenance as well as differences in the metabolism of the scion and the rootstock. It is difficult to know if a grafted plant will survive or die, moreover, there are few visual indicators of grafting success at an early stage of development ( Figure 1B ) (Tedesco et al, 2020 ). The identification of molecular markers of grafting success would be a great advantage for genetic research and rootstock selection programs.…”
Section: Introductionmentioning
confidence: 99%